Examining provider practice-level disparities in delivery outcomes among patients with a history of Cesarean Delivery - Lily McCarthy; Nicola F Tavella; Sara Wetzler; Lily Ardente; Molly Chadwick; Dexter Paul; Nikki Sabet; Toni Stern; Angela Bianco (BMC Pregnancy and Childbirth, 2024)
Abstract Background Choosing whether to pursue a trial of labor after cesarean (TOLAC) or scheduled repeat cesarean delivery (SRCD) requires prenatal assessment of risks and benefits. Providers and patients play a central role in this process. However, the influence of provider-associated characteristics on delivery methods remains unclear. We hypothesized that different provider practice groups have different obstetric outcomes in patients with one prior cesarean delivery (CD). Methods This was a retrospective cohort study of deliveries between April 29, 2015 – April 29, 2020. Subjects were divided into three cohorts: SRCD, successful VBAC, and unsuccessful VBAC (patients who chose TOLAC but had a CD). Disparities were reviewed between five different obstetric provider practice groups, determined from a breakdown of different providers delivering at the study site during the study period. Proportional differences were examined using Chi-squared tests and logistic regression models. Results 1,439 deliveries were included in the study. There were significant proportional disparities between patients in the different groups. Specifically, patients from Group D were significantly more likely to undergo successful VBAC, while patients seeing a provider from Group A were more likely to deliver by SRCD. In our multivariate analysis of successful versus unsuccessful VBAC, patients from Group D had greater odds ratios of successful VBAC compared to Group A. Patients delivered by Group E had a significantly lower odds ratio of successful VBAC. Conclusion This study suggests an association between provider practice groups and delivery outcomes among patients with one prior CD. These data contribute to a growing body of literature around patient choice in pregnancy and the interplay of patients and providers. These findings help to guide future investigations to improve outcomes among patients with a history of CD.